Indexing from thesauri to the Semantic Web - Keyser, Pierre de. (Oxford Chandos Pub., 2012)
"Indexing consists of both novel and more traditional techniques. Cutting-edge indexing techniques, such as automatic indexing, ontologies, and topic maps, were developed independently of older techniques such as thesauri, but it is now recognized that these older methods also hold expertise. Indexing describes various traditional and novel indexing techniques, giving information professionals and students of library and information sciences a broad and comprehensible introduction to indexing. This title consists of twelve chapters: an Introduction to subject readings and thesauri; Automatic indexing versus manual indexing; Techniques applied in automatic indexing of text material; Automatic indexing of images; The black art of indexing moving images; Automatic indexing of music; Taxonomies and ontologies; Metadata formats and indexing; Tagging; Topic maps; Indexing the web; and The Semantic Web."--Publisher's website.
Introduction to subject headings and thesauri -- Automatic indexing versus manual indexing -- Techniques applied in automatic indexing of text material -- Automatic indexing of images -- The black art of indexing moving images -- Automatic indexing of music -- Taxonomies and ontologies -- Metadata formats and indexing -- Tagging -- Topic maps -- Indexing the web -- The semantic web.
Keywords: Indexing